Diversity and multiplexing based on GMD algorithm - HE Zhong-tang1; AI Ju-mei2; HU Luo-quan1; ZHANG Li-jun1 (Tongxin xuebao)
The GMD-VBLAST algorithm to treat with the MIMO systems was analyzed,where the channel information at both transmitter and receiver were known.It decomposed a MIMO channel into multiple identical parallel subchannels and provided more convenient for coding/decoding schemes,which was different from conventional SVD method.The diversity and multiplexing tradeoff curve was achieved in the case of high SNR and compared with the optimal tradeoff curve and others VBLAST schemes’.The results showed that this scheme is suboptimal to the optimal but superior to the other VBLAST schemes’.